Immune Responses in Neurodegenerative Diseases - Shrestha, R; Shrestha, Shakya; Millington, O; Brewer, J; Bushell, T (Kathmandu University Medical Journal, 2015)
Neurodegenerative disease is a progressive loss of neurons from central nervous system and has a huge impact on health care system. Various causes have been proposed of which inflammation has been suggested to be a probable key factor in the most of such conditions. The involvement of immune cells including lymphocytes in such diseased condition of the CNS supports this notion. The effective therapy for these diseases has been sought for more than a half century but still lacking such therapy. On such basis this review article has mainly focussed on evidence of the involvement of immune cells in various neurodegenerative diseases including Alzheimer’s disease, Parkinson’s diseases and Multiple sclerosis and suggests a possible therapy of such diseased conditions of the CNS by the modulation of immune system.Kathmandu University Medical Journal Vol.12(1) 2014: 67-76